The Effect of E-Trust and E-Recovery on Loyalty through Consumer Satisfaction of Shopee Users in Pati Regency - Dyah Ayu Fitriana; Mochamad Edris; Sunarno (Journal of Finance and Business Digital, 2023)
This research aims to analyze the influence of e trust and e recovery on loyalty through consumer satisfaction of shopee users in Pati Regency. The data collection method uses a questionnaire. The results of the research conclude that (1) E trust has a positive and significant effect on satisfaction of Shopee users in Pati Regency (2) E recovery has a positive and significant effect on satisfaction of Shopee users in Pati Regency (3) E trust has a positive and significant effect on loyalty in Shopee users in Pati Regency (4) e recovery has a positive and significant effect on loyalty of Shopee users in Pati Regency (5) Satisfaction has a positive and significant effect on loyalty of Shopee users in Pati Regency.